Nationwide hepatitis C virus screening and treatment of adolescents in Egyptian schools. (July 2022) - Kamal, Ehab; Asem, Noha; Hassany, Mohamed; Elshishiney, Galal; Abdel-Razek, Wael; Said, Heba; Abdel Hamid, Sohair; Essam, Tamer; Rehan, Ahmed; Salah, Aysam; Saad, Tarek; Shawky, Nasr; et al.
Summary: Until 2018, Egypt had the highest prevalence of hepatitis C virus (HCV) infection globally, affecting approximately 7% of the population. Despite efforts in diagnosis and treatment since 2006, nearly 2 million individuals with chronic HCV infection had yet to be diagnosed as of early 2018. In December, 2018, a mass HCV screening campaign for adolescents aged 15–18 years was initiated. Among 3 024 325 adolescents screened, the HCV antibody seroprevalence was 11 477 (0·38%), of whom 8187 (78·7%) were HCV RNA-positive. Sustained virological response 12 weeks after completion of treatment (SVR12) was attained by 7327 (99·6%) adolescents with a fixed-dose combination of generic ledipasvir 90 mg plus sofosbuvir 400 mg. Although mass screening in this age group might not be regularly adopted by many health systems and its cost-effectiveness might be lower than the screening of adults and high-risk groups (eg, patients on haemodialysis, people who inject drugs), breaking the chain of transmission in younger populations should lead to a reduction in HCV incidence and complications, and hasten the elimination of the disease.